Parametric analysis of a cross-flow membrane-based parallel-plate liquid desiccant dehumidification system: numerical and experimental data - Bai, Hongyu; Zhu, Jie; Chen, Ziwei; Chu, Junze (Elsevier, 2018)
Operating parameters of a membrane-based parallel-plate liquid desiccant dehumidification system are investigated in this paper. The liquid desiccant and air are in a cross-flow arrangement, and separated by semi-permeable membranes to avoid carry-over problem. A numerical model is developed to simulate the system performance, and validated by experimental and analytical results. Impacts of main operating parameters on the system performance (i.e. sensible, latent and total effectiveness) are evaluated, which include dimensionless parameters (i.e. solution to air mass flow rate ratio m^* and number of heat transfer units NTU), solution properties (i.e. concentration C_sol and temperature T_sol) and inlet air conditions (i.e. temperature T_(air,in) and relative humidity 〖RH〗_(air,in)). It is found that m^* and NTU are two of the most important parameters influencing the system effectiveness. Even though the system performance can be improved by m^*and NTU, its increasing gradient is limited when m^*and NTU exceed 1 and 4 respectively. Decreasing solution temperature does not make a great improvement to the system performance, however, increasing solution concentration is a good approach to enhance the latent effectiveness without influencing the sensible effectiveness. The system shows the broad adaptability in various weather conditions, and has the ability to provide relative stable state supply air.